Spontaneous telomere to telomere fusions occur in unperturbed fission yeast cells - Almeida, Hugo (Oxford University Press, 2013)
Telomeres protect eukaryotic chromosomes from illegitimate end-to-end fusions. When this function fails, dicentric chromosomes are formed, triggering breakage-fusion-bridge cycles and genome instability. How efficient is this protection mechanism in normal cells is not fully understood. We created a positive selection assay aimed at capturing chromosome-end fusions in Schizosaccharomyces pombe. We placed telomere sequences with a head to head arrangement in an intron of a selectable marker contained on a plasmid. By linearizing the plasmid between the telomere sequences, we generated a stable mini-chromosome that fails to express the reporter gene. Whenever the ends of the mini-chromosome join, the marker gene is reconstituted and fusions are captured by direct selection. Using telomerase mutants, we recovered several fusion events that lacked telomere sequences. The end-joining reaction involved specific homologous subtelomeric sequences capable of forming hairpins, suggestive of ssDNA stabilization prior to fusing. These events occurred via microhomology-mediated end-joining (MMEJ)/single-strand annealing (SSA) repair and also required MRN/Ctp1. Strikingly, we were able to capture spontaneous telomere-to-telomere fusions in unperturbed cells. Similar to disruption of the telomere regulator Taz1/TRF2, end-joining reactions occurred via non-homologous end-joining (NHEJ) repair. Thus, telomeres undergo fusions prior to becoming critically short, possibly through transient deprotection. These dysfunction events induce chromosome instability and may underlie early tumourigenesis.